Réponses

2013-05-20T13:07:27+02:00

a) -5(2+4x)=-6(2-3x)

 

-5*2-5*4x=-6*2-6*(-3x)

-10-20x=-12+18x

-20x-18x=-12+10

-38x=-2

x=-2/-38

x=2/38

 

b) 9-3(5+2x)=4+8(1-3x)

9-3*5-3*2x=4+8*1+8*(-3x)

9-15-6x=4+8-24x

-6x+24x=4+8-9+15

18x=18

x=18/18

x=1

 

c) 1-2 (3x-4)=5x-2(3x-5)

1-2*3x-2*(-4)=5x-2*3x-2*(-5)

1-6x+8=5x-6x+10

-6x+6x-5x=10-1-8

-5x=1

x=1/-5

x=-0.2

 

d) -x-6(-5-3x)=2(-2x+9)-5

-x-6*(-5)-6*(-3x)=2*(-2x)+2*9-5

-x+30+18x=-4x+18-5

-x+18x+4x=18-5-30

21x=-17

x=-17/21

Meilleure réponse !
  • Utilisateur Brainly
2013-05-20T13:21:11+02:00

a)

-5(2+4x)=-6(2-3x)

-5*2-5*4x=-6*2-6*(-3x)

-10-20x=-12+18x

-10-20x-18x=-12+18x-18x

-10-38x=-12

-10-38x+10=-12+10

-38x=-2

x=-2/-38

 

 

b)

9-3(5+2x)=4+8(1-3x)

9-3*5-3*2x=4+8*1+8*(-3x)

9-15-6x=4+8-24x

-6-6x+24x=12-24x+24x

-6+18x=12

-6+18x-+6=12+6

18x=18

x=18/18

x=1

 

c)

1-2 (3x-4)=5x-2(3x-5)

1-2*3x-2*(-4)=5x-2*3x-2*(-5)

1-6x+8=5x-6x+10

9-6x=-1x+10

9-6x+1x=-1x+10+1x

9-5x=10

9-5x-9=10-9

-5x=1

x=1/-5

x=-0.2

 

 

d)

-x-6(-5-3x)=2(-2x+9)-5

-x-6*(-5)-6*(-3x)=2*(-2x)+2*9-5

-x+30+18x=-4x+18-5

+30+17x=-4x+13

30+17x+4x=-4x+13+4x

30+21x=13

30+21x-30=13-30

21x=-17

x=-17/21

 

voilà....... :)